Application of Power Plant 4.0: Process Digitalization and Challenges - Paryanto, Paryanto; Munyensanga, Patrick; Indrawan, Harry; Cahyo, Nur (ROTASI, 2020)
Most power plant process control concern on optimizing the power generation, reduce unplanned shutdown and reduce inventory cost. These challenges can be solved by implementing newly technology called Industry 4.0, which integrates the industrial internet of things (IIoT) and the cyber-enhanced systems as well as cloud computing. This paper presents a prototype system loop as an example of the power generation network to measure the rotating speed, number of turn and the frequency of vibration for the rotating device, humidity & temperature of the physical cooler or heater device within the plant in order to explain the interoperability principle of Industry 4.0 through the implementation of Power Plant 4.0. Base on the test results then used as a basis for identifying the challenges that will arise and the solution to implement Power Plant 4.0 with effectively and efficiently.